2002
DOI: 10.1123/jtpe.21.3.230
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Types of Walking Activities on Actual Choices by Adolescent Female Physical Education Students

Abstract: This study examined the choices made by adolescent girls in physical education classes when allowed to choose from among a variety of walking activities. Following the TARGET (Epstein, 1988; Treasure & Roberts, 1999) structures, nine walking activities were created to reflect one of four themes: social, exercise/fitness, game-like, or competition. Participants were 570 girls from 21 intact 7th and 8th grade classes from five schools in two school districts. Every 3 days for 9 days, students chose from a li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
23
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 0 publications
0
23
0
Order By: Relevance
“…In other words, girls receiving the PPS probably felt some control in dictating the skill grade they could achieve. Second, in physical education, girls have shown a stronger preference for cooperative rather than competitive activities (Prusak & Darst, 2002). The AAHPERD skill test, primarily due to its norm-or peer-referenced criteria for success, likely created a more competitive than cooperative environment thus reducing girls' situational motivation.…”
Section: Gender and Skill Testingmentioning
confidence: 99%
See 4 more Smart Citations
“…In other words, girls receiving the PPS probably felt some control in dictating the skill grade they could achieve. Second, in physical education, girls have shown a stronger preference for cooperative rather than competitive activities (Prusak & Darst, 2002). The AAHPERD skill test, primarily due to its norm-or peer-referenced criteria for success, likely created a more competitive than cooperative environment thus reducing girls' situational motivation.…”
Section: Gender and Skill Testingmentioning
confidence: 99%
“…For example, previous studies have found that when teachers use methodologies specifically intended to increase student perceptions of choice (Prusak et al, 2004;Ward, Wilkinson, Graser, & Prusak, 2008), perceived competence (Lee, Fredenberg, Belcher, & Cleveland, 1999), and sociality (Prusak & Darst, 2002;Reeve & Sikenius, 1994), that such practices have a positive effect on situational motivation in PE. Self-determination theory provides a particularly useful theory in that it proposes that life-long, motivated behaviors (such as physical activity patterns) are shaped and influenced by the collective and formative success in situation-and context-specific experiences, such as those in PE (Guay, Mageau, & Vallerand, 2003).…”
mentioning
confidence: 99%
See 3 more Smart Citations